(3GdfLe ef cdGe SjO GdYQH hGdYLes - (3CMeO Hf eYO Hf YjSi Hf hcjd GdJLjHj, GHf GdCbdjTj , CHh GdYHGS,J (B550 (3g` s
(3ChdgG (B:s
(3LGeY Gdcde afSN TQYI LejY TQGFY GdCee MLI bGWYI Ydi LejY GdYQH hGdYLe s
(3BNQgG (B:s
(3Gddge GgOfi ajef gOjJ hYGafi ajef YGajJ hJhdfi ajef JhdjJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B259 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B181s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1930s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
(3MGdI GdfSNI LjOI s
Keywords: (3GdMOjK h GdeUWdMs